High temperature suspension stabilizer for cementing and preparation method thereof

By preparing high-temperature resistant anion and cationic copolymers and compounding them with high-temperature carboxymethylcellulose to form a tight crosslinked network structure, the problem of poor suspension stability of cement slurry at high temperature is solved, and good suspension and stability of cement slurry at high temperature is achieved.

CN117467418BActive Publication Date: 2025-04-01SICHUAN CHUANQING UNDERGROUND TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311179572.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-04-01
Estimated Expiration
2043-09-13

AI Technical Summary

Technical Problem

Under high temperature conditions, the polymer of existing cement slurry suspension stabilizers is prone to degradation, resulting in a decrease in system viscosity, loss of structural force and suspension capacity, and affecting the cementing quality.

Method used

By preparing high-temperature resistant anionic copolymer and cationic copolymer, and combining it through strong electrostatic effects between positive and negative ions, a tight cross-linked network structure is formed, enhancing the suspension ability of cement particles. At the same time, high-temperature resistant carboxymethylcellulose is added to further improve stability.

Benefits of technology

Under high temperature conditions, the prepared cementing high-temperature suspension stabilizer can maintain good stable suspension effect, improve the high-temperature resistance and suspension stability of the cement slurry, and ensure the cementing quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004446738980000111
    Figure BDA0004446738980000111
  • Figure BDA0004446738980000121
    Figure BDA0004446738980000121
Patent Text Reader

Abstract

The invention relates to the technical field of suspension stabilizers, and in particular to a high-temperature suspension stabilizer for cementing and a preparation method thereof. In the process of preparing a high-temperature resistant anionic copolymer and a high-temperature resistant cationic copolymer, N,N-dimethylacrylamide with high-temperature resistance and a self-made long-chain alkyl silicone oil with hydrophobicity are added to the preparation of the high-temperature resistant anionic copolymer and the high-temperature resistant cationic copolymer, so that the prepared high-temperature resistant anionic copolymer and the high-temperature resistant cationic copolymer respectively have relatively stable high-temperature resistance and hydrophobicity, and the high-temperature resistant anionic copolymer and the high-temperature resistant cationic copolymer are compounded through the strong electrostatic effect between positive and negative ions, so that a compact cross-linked network structure can be formed between polymer molecules, so that cement particles can be suspended, and the molecular structure can be kept unchanged at high temperature, so that the stabilizer has good thickening effect and high-temperature resistance, and the added high-temperature resistant carboxymethyl cellulose can improve the suspension stability of the high-temperature suspension stabilizer for cementing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of suspension stabilizers, and in particular to a high-temperature suspension stabilizer for cementing and a preparation method thereof. Background Art

[0002] Deep formations have become an important research area for oil and gas resource exploration and large-scale reserve increase, but the high temperature environment in deep formations makes the settlement instability of oil well cement more prominent, which will seriously endanger the production and safety of oil and gas wells. Therefore, it is very important to control the settlement stability of cement slurry under high temperature. The free liquid and solid phase settlement caused by the instability of cement slurry have a great influence on the cementing quality, which is more obvious in cementing in high-angle sections and horizontal sections. The free liquid and solid phase settlement will cause excessive permeability of cement stone in the upper part of the well section, and even produce micro gaps, resulting in interlayer communication and channeling. However, when using low-density cement slurry, the relative density difference between the lightening material and the cement particles is usually large, and it is easy to float and aggregate freely, causing the cement slurry to be unstable. The same problem also exists in high-density cement slurry. In addition, if the downhole temperature is high, due to the failure of the decomposition of the polymer, it will also cause insufficient suspension capacity of the slurry, resulting in settlement and free liquid, affecting the cement slurry bonding quality in the later stage. Therefore, good cement slurry stability is very important, and adding suspension stabilizers is a common practice to improve the stability of cement slurry.

[0003] Common substances that play a role in suspension stabilization include biopolysaccharides, cellulose derivatives, natural polymers, and synthetic polymer copolymers. By forming a network structure in the cement slurry system, the movement of particles in the water slurry system is controlled to achieve the purpose of maintaining the stability of the system. However, under high temperature conditions, polymers are prone to degradation, the viscosity of the system decreases, and the structural force and suspension ability are lost. If the existing polymers can be modified and improved so that they can have better high temperature resistance while maintaining the original stable cement slurry suspension performance, they can be better applied in the field of cement slurry suspension stabilization. Therefore, how to improve the polymer while maintaining its original characteristics has become a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention

[0004] Technical issues solved

[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a high-temperature suspension stabilizer for cementing and a preparation method thereof, so that the prepared high-temperature suspension stabilizer for cementing still has a good stabilizing suspension effect under high temperature conditions.

[0006] Technical Solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A method for preparing a high-temperature suspension stabilizer for cementing, the method comprising the following steps:

[0009] Step 1. According to the molar ratio of 5:2:2:1:1, the calculated amount of 2-acrylamido-methylpropanesulfonic acid, acrylamide, N-vinyl pyrrolidone, N,N-dimethylacrylamide and homemade long-chain alkyl silicone oil are weighed and poured into a flask filled with deionized water. Under the condition of stirring in an ice bath, sodium hydroxide solution is added to adjust the pH value to 7 and nitrogen is introduced for 30-40 minutes. Then, the mixture is transferred to a water bath at 65°C and potassium persulfate is added. The mixture is reacted at a constant temperature for 10-12 hours. The result is recorded as a high temperature resistant anionic copolymer, wherein the weight of deionized water is 75-80% of the total weight of the high temperature resistant anionic copolymer, and the weight of potassium persulfate is 0.3-0.5% of the total weight of the high temperature resistant anionic copolymer;

[0010] Step 2, weighing calculated amounts of acrylamide, N, N-dimethyloctadecyl allyl ammonium chloride, N-vinyl pyrrolidone, N, N-dimethyl acrylamide and homemade long-chain alkyl silicone oil in a molar ratio of 6:1:4:1:2, dissolving them in deionized water in turn, then heating to 40°C and adding initiator components, reacting at 60°C for 22-24h, and the obtained product is recorded as a high temperature resistant cationic copolymer, wherein the weight of deionized water is 78-80% of the total weight of the high temperature resistant cationic copolymer, and the weight of the initiator component is 1-2% of the total weight of the high temperature resistant cationic copolymer;

[0011] Step 3, mix the high temperature resistant anionic copolymer in Step 1, the high temperature resistant cationic copolymer in Step 2 and the high temperature resistant carboxymethyl cellulose in a weight ratio of 3:2:1, stir at a stirring speed of 500-600r / min for 30-40min, then add anhydrous ethanol for precipitation, repeat the precipitation 3 times, vacuum dry and crush the precipitated product, and the obtained product is a high temperature suspension stabilizer for cementing.

[0012] Furthermore, the preparation method of the homemade long-chain alkyl silicone oil in Step 1 and Step 2 is:

[0013] S1, weigh 15 parts by weight of tetramethylcyclotetrasiloxane and 12 parts by weight of pentamethylcyclopentasiloxane, pour them into a four-necked flask equipped with a stirrer, a dropping funnel, a thermometer and a condenser, heat to boiling and keep warm for 30 minutes, then add 3 parts by weight of hexamethyldisiloxane and 0.1 parts by weight of aluminum sulfate dihydrate, and heat to 120-130° C. under stirring. After reacting for 24 hours, the obtained product is recorded as methyl-hydrogen-polysiloxane;

[0014] S2. Pour 30 parts by weight of decene and 10 parts by weight of chloroplatinic acid-isopropanol solution into a four-necked flask equipped with a stirrer, a dropping funnel, a thermometer and a condenser, heat to 70°C and then dropwise add 8 parts by weight of the methyl-hydrogen-polysiloxane in S1, then continue to heat to 110°C under stirring, react for 3-5 hours, and then distill under reduced pressure to obtain the homemade long-chain alkyl silicone oil.

[0015] Furthermore, the stirring speed in S1 and S2 is 200-300 r / min.

[0016] Furthermore, the chloroplatinic acid-isopropanol solution in S2 is prepared by mixing chloroplatinic acid and isopropanol in a material-liquid ratio of 1:19 (g / mL).

[0017] Furthermore, the stirring speed in Step 1 is 300-500 r / min, and the mass fraction of the sodium hydroxide solution in Step 1 is 35%.

[0018] Furthermore, the initiator component in Step 2 is prepared by mixing potassium persulfate and sodium bisulfite in an equal weight ratio.

[0019] Furthermore, the preparation method of the high temperature resistant carboxymethyl cellulose in Step 3 comprises the following steps:

[0020] Step 1, weighing 1 part by weight of triphenyl phosphite, 20 parts by weight of cellulose and 18 parts by weight of sodium hydroxide, pouring them into 100 parts by weight of ethanol aqueous solution, reacting them at a temperature of 35° C. for 90 minutes for alkalization, and removing the filtrate by suction filtration to obtain alkalized cellulose;

[0021] Step 2, dissolving chloroacetic acid in an ethanol aqueous solution at a material-liquid ratio of 4:3 (g / mL) to prepare a chloroacetic acid-ethanol solution, then soaking the alkalized fiber in step 1 in the chloroacetic acid-ethanol solution, adding a sodium hydroxide solution whose weight is 5% of the chloroacetic acid-ethanol solution, heating to 55° C. and keeping warm for 20 minutes, then heating to 75° C. and keeping warm for 40 minutes, and finally heating to 78° C. and keeping warm for 10 minutes, and the result is recorded as a mixed component;

[0022] Step 3, cooling the mixed components in step 2 to room temperature, adding hydrochloric acid to adjust the pH value to 7-8, washing the precipitate with anhydrous ethanol after centrifugation, crushing and passing through a 50-mesh sieve after vacuum drying, and obtaining the high-temperature resistant carboxymethyl cellulose.

[0023] Furthermore, the concentration of the ethanol aqueous solution in step 1 and step 2 is 95%.

[0024] Furthermore, the mass fraction of the sodium hydroxide solution in step 2 is 45%.

[0025] A high-temperature suspension stabilizer for well cementing, wherein the raw material components of the high-temperature suspension stabilizer for well cementing include: 2-acrylamido-methylpropanesulfonic acid, acrylamide, N-vinyl pyrrolidone, N,N-dimethylacrylamide, N,N-dimethyloctadecyl allyl ammonium chloride, tetramethylcyclotetrasiloxane, pentamethylcyclopentasiloxane, hexamethyldisiloxane, aluminum sulfate dihydrate, decene, chloroplatinic acid, isopropanol, sodium hydroxide solution with a mass fraction of 35%, potassium persulfate, sodium bisulfite, triphenyl phosphite, cellulose, sodium hydroxide solution with a mass fraction of 45%, chloroacetic acid, hydrochloric acid, 95% ethanol aqueous solution and anhydrous ethanol.

[0026] Beneficial Effects

[0027] The present invention provides a high-temperature suspension stabilizer for cementing and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. In the process of preparing the high temperature resistant anionic copolymer and the high temperature resistant cationic copolymer, the present invention adds N,N-dimethylacrylamide with high temperature resistance and self-made long-chain alkyl silicone oil with hydrophobicity, so that the prepared high temperature resistant anionic copolymer and the high temperature resistant cationic copolymer have relatively stable high temperature resistance and hydrophobicity, respectively. The high temperature resistant anionic copolymer and the high temperature resistant cationic copolymer are compounded through the strong electrostatic effect between positive and negative ions, so that a tight cross-linked network structure can be formed between polymer molecules, thereby suspending cement particles, and keeping the molecular structure unchanged at high temperature, and having good thickening effect and high temperature resistance.

[0029] 2. In the preparation process of the high-temperature suspension stabilizer for cementing, the present invention adds high-temperature resistant carboxymethyl cellulose to make it cross-linked with the high-temperature resistant anionic copolymer and the high-temperature resistant cationic copolymer, which can not only enhance the high-temperature resistance of the high-temperature suspension stabilizer for cementing to a certain extent, but also improve the suspension stability of the high-temperature suspension stabilizer for cementing by adding the high-temperature resistant carboxymethyl cellulose, thereby making the prepared high-temperature suspension stabilizer for cementing have better market application value. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The present invention will be further described below in conjunction with the embodiments.

[0032] Example 1

[0033] The present embodiment provides a method for preparing a high-temperature suspension stabilizer for cementing, the preparation method comprising the following steps:

[0034] Step 1. According to the molar ratio of 5:2:2:1:1, the calculated amount of 2-acrylamido-methylpropanesulfonic acid, acrylamide, N-vinyl pyrrolidone, N,N-dimethylacrylamide and homemade long-chain alkyl silicone oil were weighed and poured into a flask filled with deionized water. Under the condition of stirring in an ice bath, sodium hydroxide solution was added to adjust the pH value to 7 and nitrogen was introduced for 30 minutes. Then, the mixture was transferred to a water bath at 65°C and potassium persulfate was added. The mixture was reacted at a constant temperature for 10 hours. The obtained mixture was recorded as a high temperature resistant anionic copolymer, wherein the weight of deionized water was 75% of the total weight of the high temperature resistant anionic copolymer, and the weight of potassium persulfate was 0.3% of the total weight of the high temperature resistant anionic copolymer.

[0035] Step 2, according to the molar ratio of 6:1:4:1:2, weigh the calculated amount of acrylamide, N, N-dimethyl octadecyl allyl ammonium chloride, N-vinyl pyrrolidone, N, N-dimethyl acrylamide and homemade long-chain alkyl silicone oil, dissolve them in deionized water in turn, then heat to 40°C and add initiator component, react at 60°C for 22h, and the obtained product is recorded as high temperature resistant cationic copolymer, wherein the weight of deionized water is 78% of the total weight of the high temperature resistant cationic copolymer, and the weight of the initiator component is 1% of the total weight of the high temperature resistant cationic copolymer;

[0036] Step 3, mix the high temperature resistant anionic copolymer in Step 1, the high temperature resistant cationic copolymer in Step 2 and the high temperature resistant carboxymethyl cellulose in a weight ratio of 3:2:1, stir at a stirring speed of 500 r / min for 30 minutes, then add anhydrous ethanol for precipitation, repeat the precipitation three times, vacuum dry and crush the precipitated product, and the obtained product is a high temperature suspension stabilizer for cementing.

[0037] The preparation method of the homemade long-chain alkyl silicone oil in Step 1 and Step 2 is:

[0038] S1, weigh 15 parts by weight of tetramethylcyclotetrasiloxane and 12 parts by weight of pentamethylcyclopentasiloxane, pour them into a four-necked flask equipped with a stirrer, a dropping funnel, a thermometer and a condenser, heat to boiling and keep warm for 30 minutes, then add 3 parts by weight of hexamethyldisiloxane and 0.1 parts by weight of aluminum sulfate dihydrate, and heat to 120° C. under stirring. After reacting for 24 hours, the result is recorded as methyl-hydrogen-polysiloxane;

[0039] S2. Pour 30 parts by weight of decene and 10 parts by weight of chloroplatinic acid-isopropanol solution into a four-necked flask equipped with a stirrer, a dropping funnel, a thermometer and a condenser, heat to 70°C and then drop 8 parts by weight of the methyl-hydrogen-polysiloxane in S1, then continue to heat to 110°C under stirring, react for 3 hours, and then distill under reduced pressure to obtain the homemade long-chain alkyl silicone oil.

[0040] The stirring speed of stirring in S1 and S2 is 200 r / min.

[0041] The chloroplatinic acid-isopropanol solution in S2 is prepared by mixing chloroplatinic acid and isopropanol in a solid-liquid ratio of 1:19 (g / mL).

[0042] The stirring speed in Step 1 is 300 r / min, and the mass fraction of the sodium hydroxide solution in Step 1 is 35%.

[0043] In step 2, the initiator component is prepared by mixing potassium persulfate and sodium bisulfite in an equal weight ratio.

[0044] The preparation method of the high temperature resistant carboxymethyl cellulose in Step 3 comprises the following steps:

[0045] Step 1, weighing 1 part by weight of triphenyl phosphite, 20 parts by weight of cellulose and 18 parts by weight of sodium hydroxide, pouring them into 100 parts by weight of ethanol aqueous solution, reacting them at a temperature of 35° C. for 90 minutes for alkalization, and removing the filtrate by suction filtration to obtain alkalized cellulose;

[0046] Step 2, dissolving chloroacetic acid in an ethanol aqueous solution at a material-liquid ratio of 4:3 (g / mL) to prepare a chloroacetic acid-ethanol solution, then soaking the alkalized fiber in step 1 in the chloroacetic acid-ethanol solution, adding a sodium hydroxide solution whose weight is 5% of the chloroacetic acid-ethanol solution, heating to 55° C. and keeping warm for 20 minutes, then heating to 75° C. and keeping warm for 40 minutes, and finally heating to 78° C. and keeping warm for 10 minutes, and the result is recorded as a mixed component;

[0047] Step 3, cooling the mixed components in step 2 to room temperature, adding hydrochloric acid to adjust the pH value to 7, washing the precipitate with anhydrous ethanol after centrifugation, crushing and passing through a 50-mesh sieve after vacuum drying, and obtaining the high-temperature resistant carboxymethyl cellulose.

[0048] The concentration of the ethanol aqueous solution in step 1 and step 2 is 95%.

[0049] The mass fraction of the sodium hydroxide solution in step 2 is 45%.

[0050] The invention discloses a high-temperature suspension stabilizer for cementing. The raw material components of the high-temperature suspension stabilizer for cementing include: 2-acrylamido-methylpropanesulfonic acid, acrylamide, N-vinyl pyrrolidone, N,N-dimethylacrylamide, N,N-dimethyloctadecyl allyl ammonium chloride, tetramethylcyclotetrasiloxane, pentamethylcyclopentasiloxane, hexamethyldisiloxane, aluminum sulfate dihydrate, decene, chloroplatinic acid, isopropanol, sodium hydroxide solution with a mass fraction of 35%, potassium persulfate, sodium bisulfite, triphenyl phosphite, cellulose, sodium hydroxide solution with a mass fraction of 45%, chloroacetic acid, hydrochloric acid, 95% ethanol aqueous solution and anhydrous ethanol.

[0051] Example 2

[0052] The present embodiment provides a method for preparing a high-temperature suspension stabilizer for cementing, the preparation method comprising the following steps:

[0053] Step 1. According to the molar ratio of 5:2:2:1:1, the calculated amount of 2-acrylamido-methylpropanesulfonic acid, acrylamide, N-vinyl pyrrolidone, N,N-dimethylacrylamide and homemade long-chain alkyl silicone oil were weighed and poured into a flask filled with deionized water. Under the condition of stirring in an ice bath, sodium hydroxide solution was added to adjust the pH value to 7 and nitrogen was introduced for 40 minutes. Then, the mixture was transferred to a water bath at 65°C and potassium persulfate was added. The mixture was reacted at a constant temperature for 12 hours. The obtained mixture was recorded as a high temperature resistant anionic copolymer, wherein the weight of deionized water was 80% of the total weight of the high temperature resistant anionic copolymer, and the weight of potassium persulfate was 0.5% of the total weight of the high temperature resistant anionic copolymer.

[0054] Step 2, according to the molar ratio of 6:1:4:1:2, weigh the calculated amount of acrylamide, N, N-dimethyl octadecyl allyl ammonium chloride, N-vinyl pyrrolidone, N, N-dimethyl acrylamide and homemade long-chain alkyl silicone oil, dissolve them in deionized water in turn, then heat to 40°C and add initiator component, react at 60°C for 24h, and the obtained product is recorded as high temperature resistant cationic copolymer, wherein the weight of deionized water is 80% of the total weight of the high temperature resistant cationic copolymer, and the weight of the initiator component is 2% of the total weight of the high temperature resistant cationic copolymer;

[0055] Step 3, mix the high temperature resistant anionic copolymer in Step 1, the high temperature resistant cationic copolymer in Step 2 and the high temperature resistant carboxymethyl cellulose in a weight ratio of 3:2:1, stir at a stirring speed of 600 r / min for 40 minutes, then add anhydrous ethanol for precipitation, repeat the precipitation three times, vacuum dry and crush the precipitated product, and the obtained product is a high temperature suspension stabilizer for cementing.

[0056] The preparation method of the homemade long-chain alkyl silicone oil in Step 1 and Step 2 is:

[0057] S1, weigh 15 parts by weight of tetramethylcyclotetrasiloxane and 12 parts by weight of pentamethylcyclopentasiloxane, pour them into a four-necked flask equipped with a stirrer, a dropping funnel, a thermometer and a condenser, heat to boiling and keep warm for 30 minutes, then add 3 parts by weight of hexamethyldisiloxane and 0.1 parts by weight of aluminum sulfate dihydrate, and heat to 130° C. under stirring. After reacting for 24 hours, the result is recorded as methyl-hydrogen-polysiloxane;

[0058] S2. Pour 30 parts by weight of decene and 10 parts by weight of chloroplatinic acid-isopropanol solution into a four-necked flask equipped with a stirrer, a dropping funnel, a thermometer and a condenser, heat to 70°C and then dropwise add 8 parts by weight of the methyl-hydrogen-polysiloxane in S1, then continue to heat to 110°C under stirring, react for 5 hours, and obtain the homemade long-chain alkyl silicone oil by vacuum distillation.

[0059] The stirring speed of stirring in S1 and S2 is 300 r / min.

[0060] The chloroplatinic acid-isopropanol solution in S2 is prepared by mixing chloroplatinic acid and isopropanol in a solid-liquid ratio of 1:19 (g / mL).

[0061] The stirring speed in Step 1 is 500 r / min, and the mass fraction of the sodium hydroxide solution in Step 1 is 35%.

[0062] In step 2, the initiator component is prepared by mixing potassium persulfate and sodium bisulfite in an equal weight ratio.

[0063] The preparation method of the high temperature resistant carboxymethyl cellulose in Step 3 comprises the following steps:

[0064] Step 1, weighing 1 part by weight of triphenyl phosphite, 20 parts by weight of cellulose and 18 parts by weight of sodium hydroxide, pouring them into 100 parts by weight of ethanol aqueous solution, reacting them at a temperature of 35° C. for 90 minutes for alkalization, and removing the filtrate by suction filtration to obtain alkalized cellulose;

[0065] Step 2, dissolving chloroacetic acid in an ethanol aqueous solution at a material-liquid ratio of 4:3 (g / mL) to prepare a chloroacetic acid-ethanol solution, then soaking the alkalized fiber in step 1 in the chloroacetic acid-ethanol solution, adding a sodium hydroxide solution whose weight is 5% of the chloroacetic acid-ethanol solution, heating to 55° C. and keeping warm for 20 minutes, then heating to 75° C. and keeping warm for 40 minutes, and finally heating to 78° C. and keeping warm for 10 minutes, and the result is recorded as a mixed component;

[0066] Step 3, cooling the mixed components in step 2 to room temperature, adding hydrochloric acid to adjust the pH value to 8, washing the precipitate with anhydrous ethanol after centrifugation, crushing and passing through a 50-mesh sieve after vacuum drying, and obtaining high-temperature resistant carboxymethyl cellulose.

[0067] The concentration of the ethanol aqueous solution in step 1 and step 2 is 95%.

[0068] The mass fraction of the sodium hydroxide solution in step 2 is 45%.

[0069] The invention discloses a high-temperature suspension stabilizer for cementing. The raw material components of the high-temperature suspension stabilizer for cementing include: 2-acrylamido-methylpropanesulfonic acid, acrylamide, N-vinyl pyrrolidone, N,N-dimethylacrylamide, N,N-dimethyloctadecyl allyl ammonium chloride, tetramethylcyclotetrasiloxane, pentamethylcyclopentasiloxane, hexamethyldisiloxane, aluminum sulfate dihydrate, decene, chloroplatinic acid, isopropanol, sodium hydroxide solution with a mass fraction of 35%, potassium persulfate, sodium bisulfite, triphenyl phosphite, cellulose, sodium hydroxide solution with a mass fraction of 45%, chloroacetic acid, hydrochloric acid, 95% ethanol aqueous solution and anhydrous ethanol.

[0070] Example 3

[0071] The present embodiment provides a method for preparing a high-temperature suspension stabilizer for cementing, the preparation method comprising the following steps:

[0072] Step 1. According to the molar ratio of 5:2:2:1:1, the calculated amount of 2-acrylamido-methylpropanesulfonic acid, acrylamide, N-vinyl pyrrolidone, N,N-dimethylacrylamide and homemade long-chain alkyl silicone oil were weighed and poured into a flask filled with deionized water. Under the condition of stirring in an ice bath, sodium hydroxide solution was added to adjust the pH value to 7 and nitrogen was introduced for 35 minutes. Then, the mixture was transferred to a water bath at 65°C and potassium persulfate was added. The mixture was reacted at a constant temperature for 11 hours. The obtained mixture was recorded as a high temperature resistant anionic copolymer, wherein the weight of deionized water was 78% of the total weight of the high temperature resistant anionic copolymer, and the weight of potassium persulfate was 0.4% of the total weight of the high temperature resistant anionic copolymer.

[0073] Step 2, according to the molar ratio of 6:1:4:1:2, weigh the calculated amount of acrylamide, N, N-dimethyl octadecyl allyl ammonium chloride, N-vinyl pyrrolidone, N, N-dimethyl acrylamide and homemade long-chain alkyl silicone oil, dissolve them in deionized water in turn, then heat to 40°C and add initiator component, react at 60°C for 23h, and the obtained product is recorded as high temperature resistant cationic copolymer, wherein the weight of deionized water is 79% of the total weight of the high temperature resistant cationic copolymer, and the weight of the initiator component is 2% of the total weight of the high temperature resistant cationic copolymer;

[0074] Step 3, mix the high temperature resistant anionic copolymer in Step 1, the high temperature resistant cationic copolymer in Step 2 and the high temperature resistant carboxymethyl cellulose in a weight ratio of 3:2:1, stir at a stirring speed of 600 r / min for 35 minutes, then add anhydrous ethanol for precipitation, repeat the precipitation three times, vacuum dry and crush the precipitated product, and the obtained product is a high temperature suspension stabilizer for cementing.

[0075] The preparation method of the homemade long-chain alkyl silicone oil in Step 1 and Step 2 is:

[0076] S1, weigh 15 parts by weight of tetramethylcyclotetrasiloxane and 12 parts by weight of pentamethylcyclopentasiloxane, pour them into a four-necked flask equipped with a stirrer, a dropping funnel, a thermometer and a condenser, heat to boiling and keep warm for 30 minutes, then add 3 parts by weight of hexamethyldisiloxane and 0.1 parts by weight of aluminum sulfate dihydrate, raise the temperature to 125°C under stirring, and react for 24 hours to obtain methyl-hydrogen-polysiloxane;

[0077] S2. Pour 30 parts by weight of decene and 10 parts by weight of chloroplatinic acid-isopropanol solution into a four-necked flask equipped with a stirrer, a dropping funnel, a thermometer and a condenser, heat to 70°C and then drop 8 parts by weight of the methyl-hydrogen-polysiloxane in S1, then continue to heat to 110°C under stirring, react for 4 hours, and then distill under reduced pressure to obtain the homemade long-chain alkyl silicone oil.

[0078] The stirring speed of stirring in S1 and S2 is 300 r / min.

[0079] The chloroplatinic acid-isopropanol solution in S2 is prepared by mixing chloroplatinic acid and isopropanol in a solid-liquid ratio of 1:19 (g / mL).

[0080] The stirring speed of the stirring in Step 1 is 400 r / min, and the mass fraction of the sodium hydroxide solution in Step 1 is 35%.

[0081] In step 2, the initiator component is prepared by mixing potassium persulfate and sodium bisulfite in an equal weight ratio.

[0082] The preparation method of the high temperature resistant carboxymethyl cellulose in Step 3 comprises the following steps:

[0083] Step 1, weighing 1 part by weight of triphenyl phosphite, 20 parts by weight of cellulose and 18 parts by weight of sodium hydroxide, pouring them into 100 parts by weight of ethanol aqueous solution, reacting them at a temperature of 35° C. for 90 minutes for alkalization, and removing the filtrate by suction filtration to obtain alkalized cellulose;

[0084] Step 2, dissolving chloroacetic acid in an ethanol aqueous solution at a material-liquid ratio of 4:3 (g / mL) to prepare a chloroacetic acid-ethanol solution, then soaking the alkalized fiber in step 1 in the chloroacetic acid-ethanol solution, adding a sodium hydroxide solution whose weight is 5% of the chloroacetic acid-ethanol solution, heating to 55° C. and keeping warm for 20 minutes, then heating to 75° C. and keeping warm for 40 minutes, and finally heating to 78° C. and keeping warm for 10 minutes, and the result is recorded as a mixed component;

[0085] Step 3, cooling the mixed components in step 2 to room temperature, adding hydrochloric acid to adjust the pH value to 8, washing the precipitate with anhydrous ethanol after centrifugation, crushing and passing through a 50-mesh sieve after vacuum drying, and obtaining high-temperature resistant carboxymethyl cellulose.

[0086] The concentration of the ethanol aqueous solution in step 1 and step 2 is 95%.

[0087] The mass fraction of the sodium hydroxide solution in step 2 is 45%.

[0088] The invention discloses a high-temperature suspension stabilizer for cementing. The raw material components of the high-temperature suspension stabilizer for cementing include: 2-acrylamido-methylpropanesulfonic acid, acrylamide, N-vinyl pyrrolidone, N,N-dimethylacrylamide, N,N-dimethyloctadecyl allyl ammonium chloride, tetramethylcyclotetrasiloxane, pentamethylcyclopentasiloxane, hexamethyldisiloxane, aluminum sulfate dihydrate, decene, chloroplatinic acid, isopropanol, sodium hydroxide solution with a mass fraction of 35%, potassium persulfate, sodium bisulfite, triphenyl phosphite, cellulose, sodium hydroxide solution with a mass fraction of 45%, chloroacetic acid, hydrochloric acid, 95% ethanol aqueous solution and anhydrous ethanol.

[0089] Comparative Example 1

[0090] The high-temperature suspension stabilizer for cementing and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, the main difference being that the homemade long-chain alkyl silicone oil in Example 1 is not added during the preparation of the high-temperature resistant anionic copolymer in Comparative Example 1.

[0091] Comparative Example 2

[0092] The high-temperature suspension stabilizer for cementing and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that the homemade long-chain alkyl silicone oil in Example 1 is not added during the preparation of the high-temperature resistant cationic copolymer in Comparative Example 2.

[0093] Comparative Example 3

[0094] The high-temperature suspension stabilizer for cementing and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that the high-temperature resistant carboxymethyl cellulose in Example 1 is not added during the preparation of the high-temperature resistant cationic copolymer in Comparative Example 3.

[0095] Performance Testing

[0096] The high-temperature suspension stabilizers for cementing prepared in Examples 1-3 are respectively marked as Example 1, Example 2 and Example 3, and the high-temperature suspension stabilizers for cementing prepared in Comparative Examples 1-3 are respectively marked as Comparative Example 1, Comparative Example 2 and Comparative Example 3, and then the performance of Examples 1-3 and Comparative Examples 1-3 is tested.

[0097] The specific detection methods are as follows:

[0098] 1. Prepare and maintain cement slurry with reference to the national standard GB / T19139-2012 "Test Method for Oil Well Cement", add 3% by mass of Examples 1-3 and Comparative Examples 1-3 to the cement slurry, and measure the density of the cement slurry with Examples 1-3 and Comparative Examples 1-3, and the specific data are recorded in Table 1;

[0099] 2. Examples 1-3 and Comparative Examples 1-3 were heated to 150°C, 400°C and 600°C, respectively, and the mass loss rates at 150°C, 400°C and 600°C were recorded, respectively. The specific data are recorded in Table 2.

[0100]

[0101] Table 1

[0102]

[0103] Table 2

[0104] It can be seen from the data in the above table that the upper density and the lower density of the cement slurry to which the high-temperature suspension stabilizer for cementing in Examples 1-3 are added are relatively close, indicating that the difference between the density of the upper cement slurry and the density of the lower cement slurry is small, and the amount of free liquid in the cement slurry to which the high-temperature suspension stabilizer for cementing in Examples 1-3 is added is less, which indicates that the high-temperature suspension stabilizer for cementing in Examples 1-3 has a better suspension stabilization effect; secondly, the mass loss rate of the high-temperature suspension stabilizer for cementing in Examples 1-3 at 150°C, 400°C and 600°C is low, indicating that it has better high-temperature resistance and has better high-temperature resistance in actual use.

[0105] In summary, the high-temperature suspension stabilizer for cementing prepared by the present invention has better suspension effect and high-temperature resistance, and can show better market application value.

[0106] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0107] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high temperature suspension stabilizer for cementing, characterized in that: The preparation method comprises the following steps: Step 1. According to the molar ratio of 5:2:2:1:1, the calculated amount of 2-acrylamido-methylpropanesulfonic acid, acrylamide, N-vinyl pyrrolidone, N,N-dimethylacrylamide and homemade long-chain alkyl silicone oil are weighed and poured into a flask filled with deionized water. Under the condition of stirring in an ice bath, sodium hydroxide solution is added to adjust the pH value to 7 and nitrogen is introduced for 30-40 minutes. Then, the mixture is transferred to a water bath at 65°C and potassium persulfate is added. The mixture is reacted at a constant temperature for 10-12 hours. The result is recorded as a high temperature resistant anionic copolymer, wherein the weight of deionized water is 75-80% of the total weight of the high temperature resistant anionic copolymer, and the weight of potassium persulfate is 0.3-0.5% of the total weight of the high temperature resistant anionic copolymer; Step 2, weighing calculated amounts of acrylamide, N, N-dimethyloctadecyl allyl ammonium chloride, N-vinyl pyrrolidone, N, N-dimethyl acrylamide and homemade long-chain alkyl silicone oil in a molar ratio of 6:1:4:1:2, dissolving them in deionized water in turn, then heating to 40°C and adding initiator components, reacting at 60°C for 22-24h, and the obtained product is recorded as a high temperature resistant cationic copolymer, wherein the weight of deionized water is 78-80% of the total weight of the high temperature resistant cationic copolymer, and the weight of the initiator component is 1-2% of the total weight of the high temperature resistant cationic copolymer; Step 3, the high temperature resistant anionic copolymer in Step 1, the high temperature resistant cationic copolymer in Step 2 and the high temperature resistant carboxymethyl cellulose are mixed in a weight ratio of 3:2:1, stirred at a stirring speed of 500-600 r / min for 30-40 minutes, and then anhydrous ethanol is added for precipitation. After repeated precipitation for 3 times, the precipitated product is vacuum dried and crushed to obtain a high temperature suspension stabilizer for cementing; The preparation method of the homemade long-chain alkyl silicone oil in Step 1 and Step 2 is: S1, weigh 15 parts by weight of tetramethylcyclotetrasiloxane and 12 parts by weight of pentamethylcyclopentasiloxane, pour them into a four-necked flask equipped with a stirrer, a dropping funnel, a thermometer and a condenser, heat to boiling and keep warm for 30 minutes, then add 3 parts by weight of hexamethyldisiloxane and 0.1 parts by weight of aluminum sulfate dihydrate, and heat to 120-130° C. under stirring. After reacting for 24 hours, the obtained product is recorded as methyl-hydrogen-polysiloxane; S2, pour 30 parts by weight of decene and 10 parts by weight of chloroplatinic acid-isopropanol solution into a four-necked flask equipped with a stirrer, a dropping funnel, a thermometer and a condenser, heat to 70°C, then dropwise add 8 parts by weight of the methyl-hydrogen-polysiloxane in S1, then continue to heat to 110°C under stirring, react for 3-5 hours, and then distill under reduced pressure to obtain the self-made long-chain alkyl silicone oil; The preparation method of the high temperature resistant carboxymethyl cellulose in Step 3 comprises the following steps: Step 1, weighing 1 part by weight of triphenyl phosphite, 20 parts by weight of cellulose and 18 parts by weight of sodium hydroxide, pouring them into 100 parts by weight of ethanol aqueous solution, reacting them at a temperature of 35° C. for 90 minutes for alkalization, and removing the filtrate by suction filtration to obtain alkalized cellulose; Step 2, dissolving chloroacetic acid in an ethanol aqueous solution at a material-liquid ratio of 4:3 (g / mL) to prepare a chloroacetic acid-ethanol solution, then soaking the alkalized fiber in step 1 in the chloroacetic acid-ethanol solution, adding a sodium hydroxide solution whose weight is 5% of the chloroacetic acid-ethanol solution, heating to 55° C. and keeping warm for 20 minutes, then heating to 75° C. and keeping warm for 40 minutes, and finally heating to 78° C. and keeping warm for 10 minutes, and the result is recorded as a mixed component; Step 3, cooling the mixed components in step 2 to room temperature, adding hydrochloric acid to adjust the pH value to 7-8, washing the precipitate with anhydrous ethanol after centrifugation, crushing and passing through a 50-mesh sieve after vacuum drying, and obtaining the high-temperature resistant carboxymethyl cellulose.

2. The method for preparing a high-temperature suspension stabilizer for cementing according to claim 1, characterized in that: The stirring speed in S1 and S2 is 200-300 r / min.

3. The method for preparing a high-temperature suspension stabilizer for cementing according to claim 1, characterized in that: The chloroplatinic acid-isopropanol solution in S2 is prepared by mixing chloroplatinic acid and isopropanol in a solid-liquid ratio of 1:19 (g / mL).

4. The method for preparing a high-temperature suspension stabilizer for cementing according to claim 1, characterized in that: The stirring speed in Step 1 is 300-500 r / min, and the mass fraction of the sodium hydroxide solution in Step 1 is 35%.

5. The method for preparing a high-temperature suspension stabilizer for cementing according to claim 1, characterized in that: The initiator component in Step 2 is prepared by mixing potassium persulfate and sodium bisulfite in an equal weight ratio.

6. The method for preparing a high-temperature suspension stabilizer for cementing according to claim 1, characterized in that: The concentration of the ethanol aqueous solution in step 1 and step 2 is 95%.

7. The method for preparing a high-temperature suspension stabilizer for cementing according to claim 1, characterized in that: The mass fraction of the sodium hydroxide solution in step 2 is 45%.

8. The high-temperature suspension stabilizer for well cementing prepared by the method for preparing a high-temperature suspension stabilizer for well cementing according to any one of claims 1 to 7, characterized in that: The raw material components of the high-temperature suspension stabilizer for cementing include: 2-acrylamido-methylpropane sulfonic acid, acrylamide, N-vinyl pyrrolidone, N,N-dimethylacrylamide, N,N-dimethyloctadecyl allyl ammonium chloride, tetramethylcyclotetrasiloxane, pentamethylcyclopentasiloxane, hexamethyldisiloxane, aluminum sulfate dihydrate, decene, chloroplatinic acid, isopropanol, sodium hydroxide solution with a mass fraction of 35%, potassium persulfate, sodium bisulfite, triphenyl phosphite, cellulose, sodium hydroxide solution with a mass fraction of 45%, chloroacetic acid, hydrochloric acid, 95% ethanol aqueous solution and anhydrous ethanol.

Citation Information

Patent Citations

  • High-temperature-resistant high-density water-based drilling fluid and preparation method thereof

    CN112574725A

  • High-temperature-resistant polymerization suspension stabilizer cement paste for oil well cement and preparation method thereof

    CN113736016A